Rethinking exoticism in selected travel texts on Persia by Victorian women writers - Ghaderi, Farah (2013)
Exoticism in Western travel writing of the colonial era, i.e. travellers’ representations of differences encountered in the contact zone as exotic, has been found by postcolonial critics to be profoundly informed by the asymmetrical power relations between representer/colonizer and represented/colonized. As a result, it is argued that exoticism in these travel texts was appropriative, since it tended to construct the dichotomy of self/other in such a way as to justify colonial interventions in other countries. Even though, recently, there has been much scholarly work theorizing and exploring exoticism, it has skirted around the vital variable of gender by generally focusing on male-authored texts. This research seeks to rethink and re-examine exoticism by writing gender into its theorization and investigating the impact of the uncertain in-between position of Victorian women travellers in Persia as a colonial context for their responses to the Persians and their cultural practices, as well as their portrayals of self-other relations. It addresses the relatively unexplored area of Victorian women’s travel writing on Persia and focuses on Lady Sheil’s Glimpses of Life and Manners in Persia (1856), Bird Bishop’s Journeys in Persia and Kurdistan (1891) and Gertrude Bell’s Persian Pictures (1894). I draw from recent scholarship on exoticism and the notions surrounding it, such as cultural translation, appropriation of difference, reflexivity, reciprocity, colonial exoticism, Segalenian exoticism, the “static” traveller and the “exote”, among others, in the textual analysis. The political and Orientalist discourses of the time as well as the degree of political affiliation these travellers had with Britain’s colonial interest in Persia and their religious leanings are deemed crucial factors in moulding their positionality towards the differences encountered in the context of travel. Thus, they are taken into account when scrutinizing the ethnographic representations of Persians in the selected travel texts. I argue that the ambivalent in-between position of these women travellers in Persia,as an effect of Victorian gender ideology and the concomitant dual affiliations with the British self and Persian other, was positive and empowering for them in the sense that it brought about a flexible viewing positionality towards difference, allowing for a shift between the perspective of the exote and that of the static traveller. This opened up alternative perspectives, other than the conventional Orientalist ones, on the Persians and their culture, which, in turn, allowed for a more nuanced treatment of difference, adding more layering, texture and complexity to exoticism in their travel texts. My findings reveal that there is a plurality of exoticisms in the selected texts, which are too ambivalent, versatile and multi-layered to be reduced to Britain’s political control over Persia. Furthermore,they indicate that exoticism in the hands of these women travellers finds new directions and significations. Indeed, exoticism in the selected travel texts involves reflexivity and reciprocity and becomes a malleable medium for a dialogue with the self, hence questioning its pejorative connotations in colonial travel texts.